Symptom cluster management strategies and outcomes in patients with heart failure - Yodying, Weena; Siripitayakunkit, Apinya; Sumdeangrit, Bualuang; Puwanant, Sarinya (Chulalongkorn Medical Journal, 2021)
Background: Patients with heart failure have to endure different symptoms of heart failure, and the prognosis of the disease is continuous and very difficult to predict the symptoms that will happen in advance. Objective: The present descriptive research aimed to investigate symptom cluster management strategies and outcomes of symptom cluster management strategies in patients with heart failure. Methods: Dodd’s symptom management model was used as the conceptual framework of the present descriptive research. One hundred and ten patients with heart failure who sought treatment at the heart failure clinic and heart clinic of King Chulalongkorn Memorial Hospital were recruited by means of convenience sampling. The instruments used to collect to data were the demographic characteristics questionnaire and the symptom clusters, symptom cluster management, and symptom cluster management outcomes in patients with heart failure questionnaire. Results: The findings revealed that the acute symptoms included panting/shortness of breath (78.2%), insomnia/difficulty sleeping (54.5%), and chest pain (40.9%). The chronic symptoms included dyspnea on exertion (56.4%), body weight gain (48.2%), swelling in different bodily organs (48.2%). The emotional symptoms consisted of anxiety (53.6%), irritability (50.9%), and memory problems/forgetfulness (30.9%). Regarding symptom cluster management strategies, the subjects managed their acute symptoms with inhaling and exhaling slowly and deeply, lying down with the head raised, reducing fluid intake, and going to the hospital. In terms of overall symptom management outcomes, it was found that 25.0% to 48.0% of the subjects had improved symptoms. In addition, as for management of chronic symptoms, the subjects assessed the symptoms and controlled their fluid intake, adjusted the doses of diuretics, used breathing management, and at with the head raised high. On the overall, 23.0% to 36.0% of the subjects had improved symptoms. Also, when the subjects had symptoms related to the heart such as faster heartbeats/palpitation, they would call the hospital and rushed there. Conclusion: The patients with heart failure had a variety of symptoms and they selected symptom management strategies based on their perceived symptom severity or the connection they made between new symptoms and previous experiences. Some of their symptom management strategies were appropriate, whereas others were not and could be life-threatening. Therefore, nurses should offer advice on management of symptom clusters rather than emphasizing specific.